Driving sustainable consumption: how social influence, brand image, and perceived quality shape Thai Gen Z’s purchase intentions - Suttharattanagul, Sarinya L.; Manotungvorapun, Nisit (Frontiers in Sustainability, 2026)
In recent years, sustainability has been receiving attention across various academic disciplines and businesses, particularly in consumer behavior. However, limited studies employ the sociological perspective and brand image to understand how sustainable consumption can lead to purchase decisions. By drawing upon a synthesis of existing literature, this study explores an integrated model with social aspects, branding, and quality perception to examine the relationship between sustainability consumption value and purchase intentions. A quantitative approach is adopted to investigate this relationship among Thai Gen Z respondents. An online survey was conducted by a non-probability sampling method comprising 1,541 respondents, aiming to capture the attitudes, behaviors, and intentions of this demographic segment toward sustainable consumption. The findings reveal the significant relationship between sustainable consumption and purchase intention, especially the effect of brand image on the decision-making process. The findings offer valuable implications for businesses and marketers seeking to align their strategies with evolving preferences for sustainability brand image, fostering a more sustainable and responsible consumption. Additional analysis of genders recommends practical implications for marketing communications. Directions for future research are suggested for academic and consumer research.